(untitled) (Research, Society and Development, 2024)
COVID-19, caused by the SARS-CoV-2 virus, led to the excessive use of antibiotics worldwide. Despite being ineffective against viruses, antibiotics were widely used to prevent or treat the disease and its associated secondary infections. However, the excessive and inappropriate use of these medications can lead to the development of bacterial resistance, a global health problem that makes antibiotics ineffective against bacterial infections. The most prescribed drug by healthcare professionals during the pandemic was azithromycin, a macrolide widely used for bacterial infections, but in cases of COVID-19, it was indicated to alleviate the symptoms of the disease, resulting in an increase in bacterial resistance to the drug. The central question addressed in this study is: "How did the use of antibiotics to combat COVID-19 influence the increase in bacterial resistance to these medications, and how is this reflected after the end of the pandemic?" This research aims to contribute to a better understanding of the consequences of the excessive use of antibiotics during pandemics similar to COVID-19. This study aims to evaluate the increase in bacterial resistance to antibiotics used during the pandemic, especially azithromycin. To reach a conclusion regarding the main question, a detailed literature review method was used, including epidemiological and microbiological analyses, as well as studies detailing the use of azithromycin and its impacts on cases of microbiological resistance.